Kepemilikan Manajerial, Proporsi Dewan Komisaris Independen, Komite Audit dan Penghindaran Pajak - Martha, I Dewa Agung Ayu Mega Maharani; Jati, I Ketut (E-Jurnal Akuntansi; Vol 31 No 9 (2021)DO - 10.24843/EJA.2021.v31.i09.p09, 2021)
Taxes are an important source of funding for the Indonesian economy. Tax Avoidance is a company's effort to minimize the company's tax burden by looking for gaps in a country's tax weaknesses, so the scheme is legal. This study aims to obtain empirical evidence of the correlation of managerial ownership, the proportion of independent commissioners, and the audit committee on tax avoidance. The theory used is the Agency Theory. The research was carried out on mining entities that are on the IDX in the period 2017-2019, with a population of 43 entities. The number of samples obtained are 11 companies with purposive sampling method. Data collection is done by non-participant observation. The data analysis technique applied is multiple linear regression. The findings indicate that the proportion of independent commissioners has a negative effect on tax avoidance. However, managerial ownership and audit committee have no effect on tax avoidance. Keywords: Managerial Ownership; The Proportion of Independent Comissioners; Audit Committee.